Study on the hydrolytic ability of organic component in domestic waste serving for methane recovery technology - Phuoc, Nguyen Van; Thanh Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
The organic component in municipal solid waste has been considered as a valuable resource. Recent experimental data showed that organic components in municipal solid waste of Vietnam in general and Ho Chi Minh City in particular produced during anaerobic process are more than 65 %, which is advantage condition for methane recovery in anaerobic reactors. This research focused on the hydrolytic ability of organic components in municipal solid waste in laboratory scale at ambient temperature under anaerobic condition. Research results showed that appropriate pH for hydrolysis process is 10, additional NaOH dose is 10 g/L and hydrolysis time is 6 days. After hydrolysis process, soluble COD can reach 63,078±277 mg/L to 83,782±582 mg/L and hydrolysis efficiencies are in the range of 47-63 %. Hydrolysis efficiency with NaOH agent is 95 %, higher than that of when using Ca(OH)2, 74 %. This study aims to devise a comprehensive approach for selecting appropriate waste treatment technology, meeting energy reuse and biogas recovery targets. Keywords: Methane recovery, hydrolysis, domestic waste, household waste, biogas recovery.